The effect of corporate governance elements on corporate social responsibility reporting of listed companies in Vietnam - Thanh Hung Nguyen; Quynh Trang Nguyen; Duc Minh Nguyen; Thi Le (Cogent Business & Management, 2023)
This paper examines the impact of various corporate governance characteristics on the disclosure of corporate social responsibility (CSR) information in the context of developing markets during the COVID-19 pandemic. We used data from the annual reports of the top 100 companies listed on the Ho Chi Minh Stock Exchange from 2019 to 2021 to investigate the relationship between board independence, board size, CEO duality, foreign ownership, government ownership, and the disclosure level of CSR reporting. We employed a content analysis to measure CSR disclosure level by using the CSR reporting index (CSRRI) with 17 items. The panel regressions including three techniques like the pooled-ordinary least squares (OLS), fixed effects model (FEM), and random effects model (REM), were used to analyze the data, and FEM) shows its best fit to the model. The results suggest that board independence and government ownership correlate positively and significantly with companies' decisions to disclose CSR information. In contrast, board size, CEO duality, foreign ownership and was found to be insignificant. Our study extends the literature on CSR particularly in developing countries where governments play a significant role in promoting economic development. It also evaluates the CSR disclosure level of the top listed companies in Vietnam. Since then, the paper's results provide several insights to the policymakers to identify the corporate governance characteristics that will promote CSR reporting in Vietnam's listed companies.
Keywords: M14; M41; M48; 650; corporate governance; corporate social responsibility disclosure; corporate social responsibility reporting; Vietnamese listed companies